HUBUNGAN TINGKAT STRES DAN STATUS GIZI IBU DENGAN ASUPAN ASI HARIAN ANAK BADUTA DI KELURAHAN TANJUNG PINANG KOTA JAMBI - Picia Efranita; Silvia Mawarti Perdana; Herwansyah Herwansyah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Suboptimal breast milk intake can increase the risk of underweight in toddlers. Breast milk production and provision are influenced by various factors, including stress levels and maternal nutritional status. In Tanjung Pinang Village, Jambi City, the prevalence of underweight toddlers has increased, so it is necessary to study factors related to daily breast milk intake. Objective: To determine the relationship between maternal stress levels and nutritional status with daily breast milk intake of toddlers in Tanjung Pinang Village, Jambi City. Method: Quantitative research with a cross-sectional analytical design. The sample consisted of 84 mothers of toddlers selected according to the research criteria. Data analysis used the Chi-Square test. Results: The majority of mothers had normal stress levels (94.0%), mild stress (3.6%), and moderate stress (2.4%). Maternal nutritional status was dominated by mild thinness (54.8%), normal (22.6%), mild obesity (17.9%), and severe obesity (4.8%). The majority of children's daily breast milk intake was classified as insufficient (63.1%), sufficient (15.5%), and excessive (21.4%). The analysis shows that there is a relationship between stress levels and maternal nutritional status with the daily breast milk intake of toddlers.